Potensi Pengembangan Komoditas Perkebunan di Kabupaten Tapanuli Utara, Sumatera Utara - LUMBANTOBING, AGAPE; SUDARMA, I MADE; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Potential Development of Plantation Commodities  in North Tapanuli Regency, North Sumatra The occurrence of inequality of development in the smaller scope of the region in North Tapanuli Regency can prevent an increase in the regional economy. Therefore, a region needs to know the potential of commodities owned and feasible to be developed so that improvements in its economic network can be encouraged to be improved. Emphasis on development policies can be aimed at the superior commodities of this region because of their natural potential and because they have a comparative advantage. So that by optimizing the commodity capital resources can be produced with a relatively short time and the volume of production is increased. The latest data on the distribution of the plantation sub-sector of North Tapanuli Regency to the GRDP at the Basic Price of 2011-2015 shows that the average contribution is quite high on the regional economy so that it is good to be developed. The purpose of this study was to determine the potential for the development of plantation commodities in North Tapanuli. The research method used is the Location Quotient (LQ), Dynamic Location Quotient (DLQ) and Shift Share analysis using secondary data. The results of the LQ and DLQ analysis show that the main commodities of North Tapanuli Regency are the commodity of Frankincense, Arabica Coffee, Sugar Palm, Cinnamon and Cocoa. Then the shift share method shows the development of this commodity, namely Arabica Coffee has a rapid growth category, Cocoa has a developing category, Frankincense and Sugar Palm which has a category that tends to have potential, then Cinnamon has a backward category. The recommended commodity is a priority to be developed in North Tapanuli Regency, namely Arabica Coffee and Cocoa commodities because these commodities meet the criteria of the three analysis tools.